Takhrij and Syarah Hadith of Chemistry: Breathing on Hot Foods and Drinks - Sariska Patmawati; Tuti Garnasih; Titi Ratna Garnasih; Kifah Gibraltar Bey Fananie; Millatina Jurfah (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet about the prohibition of blowing hot food or drinks. This research method is qualitative through the takhrij and syarah hadith approaches with chemical analysis. The results and discussion of this study is that blowing hot food or drinks can cause acidosis in the body and attaches bacteria to the food or drink. The conclusion from the discussants of this study is that blowing food or hot drinks can be risky to the body and reduce the feasibility of consumption.